China's Motivation to Improve Bilateral Relations with South Korea After the Polemic of THAAD (Terminal High Altitude Area Defense) - Yusra, Afdhal; Yusra, Muhammad; Austin, Diah Anggraini (Palito, 2023)
North Korea's aggressiveness in launching ballistic missiles has threatened the security stability of East Asia. As a state under threat, South Korea formed a joint security partnership with the United States through the deployment of THAAD in 2016. However, China has opposed it by arguing that THAAD would threaten domestic and regional security stability. As a result, China's rejection led to the presence of the phenomenon of economic retaliation which resulted in a decrease in the value of South Korea-China bilateral trade and distrust. Nevertheless, after negotiations, the two countries decided to improve bilateral relations in 2017. This paper aims to determine China's motivation in improving bilateral relations with South Korea as a foreign policy decision after rejecting the deployment of THAAD under the guise of threatening to trigger bilateral polemics. This research will be analyzed through qualitative methods with the conceptual framework of foreign policy determinants by Shannon L. Blanton and Charles Kegley. In this conceptual framework, there are five determinants that influence foreign policy decision making namely military capabilities, economic conditions, type of government, global distributions of power, and geopolitical factors. Furthermore, Blanton & Kegley's conceptual framework identifies that each of these determinants influenced China's motivation to improving bilateral relations with South Korea after the THAAD polemic.